(untitled) (Revista Innova Educación, 2020)
This research has as a target to determine the degree of correlation between family communication and self-esteem in adolescents in urban and rural areas of the Lampa district of the Puno region (Peru). The approach is descriptive-correlational quantitative with stratified simple random probability sampling. The sample was made up of 261 adolescents of both genres aged between 12 to 17 years old. The instruments used were the Barnes & Olson Parent / Child Family Communication Questionnaire and the Rosemberg Self-Esteem Scale. The results revealed, using the Spearman’s Rho non-parametric test, an average positive correlation of 0.5 in urban areas and a considerable positive correlation of 0.8 in rural areas. In conclusion, adolescents present family communication and medium-level self-esteem, resulting in a good level of family communication leading to good self-esteem in adolescents and vice versa.